Strategy of numerical modelling for band saw blade on wood logs cutting - Bôas, Daniel Villas [UNESP]; Machado, Elder Jesus Lima; Molina, Julio Cesar; de Souza, Alexandre Jorge Duarte [UNESP]; Zavaleta-Aguilar, Elí Wilfredo [UNESP] (Universidad Nacional de Colombia, 2023)
The band saw blade, used on the wood log cutting, is exposed in service manufacturing to applications which can cause mechanical damages and affect the quality of the tool and the wood produced. To related applications, the shear stress is essential to the correct wood machining. the proposal of this paper was the numerically analyze the influence of the parallel shear force, applied vertically at the saw blade tooth, in response to the normal longitudinal tensions (σy) in service. A numeric model was constructed, by using of the commercial software based on the Finite Elements Method (FEM). In a first analysis, only a tensile stress was applied to the model on the upper edge of the blade, the deformation results obtained were used in the secondary analysis, with the simultaneous application of vertical point loads on the saw teeth.
Estrategia de modelado numérico para hojas de sierra de cinta sobre corte de troncos de madera
Keywords: numerical analysis; saw blade; shear force; wood cutting